2015
DOI: 10.1097/ccm.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Missed Central Venous Guide Wires

Abstract: Over the last decade, the number of reported instances of lost guide wires during central venous catheterization has increased rapidly. Unsupervised or improperly supervised insertions of the central catheters by trainees, distractions during insertions, and high workload are the main risk factors. A retained guide wire increases the risk and cost of additional diagnostic and therapeutic interventions, as well as imposing many minor-to-serious life-threatening complications. Continuing education along with sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…A fracture and retention of guide-wires are uncommon but a known complication of the interventional cardiology procedures. Most cases are diagnosed immediately or just after the procedures and the wires are retrieved either percutaneously or surgically [3]. Rarely, the fractured wire may be missed inadvertently at the time of procedure and diagnosed late when the patient had complications related to the retained foreign body [4], or incidentally diagnosed while diagnostic evaluation for the other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A fracture and retention of guide-wires are uncommon but a known complication of the interventional cardiology procedures. Most cases are diagnosed immediately or just after the procedures and the wires are retrieved either percutaneously or surgically [3]. Rarely, the fractured wire may be missed inadvertently at the time of procedure and diagnosed late when the patient had complications related to the retained foreign body [4], or incidentally diagnosed while diagnostic evaluation for the other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of the guidewire may occur with any type or site of vascular access, in varied hospital locations, and when different administrators perform the procedures. The incidence of complications associated with guidewire insertion has been increasing, possibly due to an increase in the vascular interventional procedures or due to increased reporting of clinical adverse events [1].…”
Section: Discussionmentioning
confidence: 99%
“…The use of intravascular interventions, including the use of central venous catheters, has been increasing over time [1]. The main indications for intravascular catheterization included hemodynamic monitoring, fluid and drug administration, parenteral nutrition, and hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Numerous case reports describe guidewire retention, 2,3,68 and a systematic literature review by Pokharel and colleagues determined that the incidence of reported guidewire retention has continued to increase. 9 Human error is often cited as the cause of this error 10 ; however, a number of factors are considered to contribute to such ‘mistakes’ such as distraction, interruptions, development of emergency situations, poor supervision, inexperienced operators and high workload. 9,11,12 Healthcare providers should aim to reduce the potential for human error where possible, and available evidence demonstrates that guidewire retention will continue to occur without the development of novel techniques incorporating engineered solutions to nudge or force safe practice.…”
Section: Introductionmentioning
confidence: 99%